2004
DOI: 10.1021/np049974l
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Structure of Antagonists of Chemokine Receptor (CCR5)

Abstract: Human CCR5 is a G-coupled receptor that binds to the envelope protein gp120 and CD4 and mediates the HIV-1 viral entry into the cells. The blockade of this binding by a small molecule receptor antagonist could lead to a new mode of action agent for HIV-1 and AIDS. Screening of natural product extracts led to the identification of anibamine (1), a novel pyridine quaternary alkaloid as a TFA salt, from Aniba sp.; ophiobolin C from fermentation extracts of fungi Mollisia sp.; and 19,20-epoxycytochalasin Q from Xy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
63
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 14 publications
(25 reference statements)
0
63
0
Order By: Relevance
“…For example Flashner et al demonstrated that the conjugated a,b-keto unsaturated group in the macrolide moiety of cytochalasin A was important for conveying antibacterial activity against Gram-positive bacteria [16]. More recently aspochalasins IϳK were found to exhibit moderate cytotoxicity against several NCI cell lines and in a separate publication 19,20-epoxycytochalsin Q was noted to be an inhibitor of CCR5 which is implicated in HIV infection [17]. Whilst the cytochalasins identified in this study are able to inhibit the activity of integrase in in vitro enzyme assays, in their current forms they are not able to inhibit the replication of HIV-1.…”
Section: Resultsmentioning
confidence: 99%
“…For example Flashner et al demonstrated that the conjugated a,b-keto unsaturated group in the macrolide moiety of cytochalasin A was important for conveying antibacterial activity against Gram-positive bacteria [16]. More recently aspochalasins IϳK were found to exhibit moderate cytotoxicity against several NCI cell lines and in a separate publication 19,20-epoxycytochalsin Q was noted to be an inhibitor of CCR5 which is implicated in HIV infection [17]. Whilst the cytochalasins identified in this study are able to inhibit the activity of integrase in in vitro enzyme assays, in their current forms they are not able to inhibit the replication of HIV-1.…”
Section: Resultsmentioning
confidence: 99%
“…Although they are found mostly on wood, some species are found on sawdust, leaf and dung or soil. The genus Xylaria has been proven to be a valuable source of bioactive agents such as chemokine receptor (CCR5) antagonist 19, 20-epoxycytochalasin Q (Jayasuriya et al 2004), the antifungal multiplolides A and B (Boonphong et al 2001), the NPY Y5 receptor antagonists xylarenals A and B (Smith et al 2002) and the cytotoxic eremophilanolides (Isaka et al 2010). Recently, we have isolated bioactive metabolites producing Xylaria spp.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations have revealed that fungi of the genus Xylaria are a rich source of structurally diverse natural products. Examples include the HIV-1 integrase inhibitor integric acid [1], the cytotoxic agents xyloallenolide A [2] and eremophilanolides [3], the antifungal metabolites multiplolides A and B [4], the acetylcholinesterase inhibitors xyloketals [5], the NPY Y5 receptor antagonists xylarenals A and B [6], the chemokine receptor antagonist 19,20-epoxycytochalasin Q [7], the anti-herpes simplex virus agent mellisol [8].…”
mentioning
confidence: 99%